Board-level gender diversity in Czech companies - Grandová, Paula (2025)
This thesis explores the relationship between board gender diversity and financial performance in Czech companies. The literature review discusses studies from Europe, America, and Asia. Although gender representation on corporate boards has improved internationally, women remain significantly underrepresented, and this trend persists in Czech companies as well. The author uses a quantitative approach to analyze data from 100 largest Czech companies across five key sectors (industry, trade and hospitality, information and communication, construction, and finance and insurance) over four years (2020-2023). Linear regression analysis was used to examine the relationship between the percentage of women on boards and two financial performance indicators: return on assets (ROA) and return on equity (ROE). The research also distinguishes between Czech-owned firms and Czech subsidiaries of foreign companies to assess the potential impact of ownership structure. The main findings confirm that female representation on corporate boards in Czech companies remains low. Furthermore, the results suggest that, in most cases, there is no statistically significant correlation between board gender diversity and ROA or ROE. These findings align with some prior studies conducted in the Czech Republic, which indicate that a higher proportion of women on boards does not automatically lead to better financial outcomes, but neither does it negatively affect performance.